God Gave Us Heaven - Bergren, Lisa Tawn; Bryant, Laura J. (Colorado Springs, Colorado : WaterBrook Press, 2008)
Little Cubs father explains to her that God created heaven, the most wonderful place, because He loves us and never wants to be far from us.
420
Accelerated Reader
Keywords: Heaven -- Fiction; Christian life -- Fiction; Polar bear -- Fiction; Bears -- Fiction; Heaven -- Fiction; Christian life -- Fiction; Polar bear -- Fiction; Bears -- Fiction